Effect of compaction pressure on densification of alumina sintered components / Muhammad Hussain Ismail ... [et al.] (Faculty of Mechanical Engineering and University Publication Centre (UPENA), 2007)
In advanced ceramic powder compaction technology, pressure during compaction is the most important factor, since it influences the physical and mechanical properties of compacted and sintered parts. This paper outlines the effect of compaction pressure on densification of compacted and sintered parts. Two grades of ceramic powders were used in this study; alumina 9620 with 3% of acrylic binder denoted as NM9620 and alumina 99 with 4% of acrylic binder denoted as NM99. Experimental work was carried out for a simple cylindrical shape compacted powder using a conventional uniaxial hydraulic compaction machine. Compaction was carried out at room temperature where 5 compaction pressure levels were applied. After compaction, the parts underwent a sintering process at a maximum temperature of 1620°C for I hour. The characteristics of the green and sintered parts, such as dimensional changes, density and hardness were studied. From this study, it showed that increasing the compaction pressure results in increasing the densities of the both green and sintered parts.